การวิเคราะห์ผู้รับสารในยุคดิจิทัล; Audiences Analysis in Digital Era - กุลจิตต์เจือวงศ์ ศุภศิลป์ (Journal of Humanities and Social Sciences (HUSOKKU), 2017)
ผู้รับสารเป็นหนึ่งในองค์ประกอบสำคัญของกระบวนการสื่อสาร เพื่อให้บรรลุวัตถุประสงค์ของการสื่อสาร องค์กรสื่อจึงควรทำการวิเคราะห์ผู้รับสารที่เปลี่ยนแปลงไปตามบริบททางสังคม โดยเฉพาะอย่างยิ่งในปัจจุบัน การก้าวเข้าสู่สังคมดิจิทัล ส่งผลให้พฤติกรรมของผู้รับสารในด้านต่างๆ ที่เปลี่ยนแปลงไป โดยเกณฑ์ที่นิยมใช้วิเคราะห์ผู้รับสาร อาทิ ลักษณะทางประชากรศาสตร์ คุณลักษณะทางจิตวิทยา และการวิเคราะห์ตามทฤษฏีการสื่อสาร โดยผู้เขียนได้เสนอแนะเชิงวิเคราะห์พฤติกรรมผู้รับสารในยุคดิจิทัลไว้ 4 ประเด็น ได้แก่ ผู้รับสารมีความเฉพาะเจาะจงมากขึ้น บทบาทของผู้รับสารในฐานะผู้ใช้สื่อ ผู้รับสารมีการเปิดรับสื่อมากขึ้น และผู้รับสารมีความกระตือรือร้นในการเปิดรับข้อมูลข่าวสาร Abstract Audience is one of the important components of communicating process to achieve the goal of communication. The media organization must analyze the audience who is changed according to the social context. Especially the world today which has entered digital era. This has affected the behavior of the audience in various aspects. The popular criteria used to analyze the audience including characteristics on population, psychology and analysis according to communicating theory. The researcher has analytically suggested the behaviors of the audience in digital era into 4 points as follows. The audience has more specification. The role of the audience as the media users. The audience is more open to the media and the audience is more eager to open up to the information.